Concept “health” in the English and Ukrainian languages - Romanyshyn, N. I.; Sherstniova, O. V.; Романишин, Н. І.; Шерстньова, О. В. (Східноєвропейський національний університет ім. Лесі Українки, 2011)
The article focuses on the investigation of the ways of the concept “Health” verbalization in English and Ukrainian, the analysis and description of the semantic features of the language means that represent the nominative field of the concept “Health” and their cognitive interpretation. Статтю присвячено дослідженню особливостей вербалізації концепту “Здоров’я” в англійській та українській мовах, аналізу семантичних особливостей мовних одиниць, що становлять номінативне поле концепту, та їхньої когнітивної інтерпретації.
Концепт “Здоров’я” в англійській та українській мовах
Keywords: concept; cognitive linguistics; cognitive interpretation; концепт; когнітивна лінгвістика; когнітивна інтерпретація